PENGEMBANGAN MEDIA AJAR BERBENTUK MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN MATEMATIKA MATERI BANGUN RUANG SISWA KELAS VI SEKOLAH DASAR - Khairunnisa Rizka (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The utilization of teaching media in the form of interactive multimedia can have a good impact in the world of education, especially the material of building space. This development study intends to produce a product in the form of teaching media in the form of interactive multimedia on the material of building space for six grade elementary school students to facilitate students in learning to produce interactive multimedia products on flatbuilding material. This study uses the Alessi & Trollip development model in which the stages are planning, designing and testing. The results of the alpha test, the product developed was declared valid. The results of the beta test explained that the teaching media in the form of interactive multimedia received practical achievements after revision. In addition, 92% of the students of SD Swata Taman Pendidikan Islam received an assessment with the achievement of completeness.